Understanding water mediated proton migration in conversion of π-bond in olefinic carbon atoms into C–N bond to form β-amino adducts. (5th November 2021) - Rathod, Prakash B.; Kumar, K.S. Ajish; Athawale, Anjali A.; Gopakumar, Gopinadhanpillai; Rao, C.V.S. Brahmmananda; Pandey, Ashok K.
Abstract: The aza-Michael reactions with a variety of substrates were conducted in water affording the quantitative yields without any external catalyst, which is contrary to that published in literature. A more rational approach to analyze this problem was by conducting this conspicuous reaction with a variety of substrates in water and the results were analyzed using advanced theoretical calculations. Our investigation on the role of water in the reaction proposed a mechanism wherein water plays dual role both as medium as well as catalyst to facilitate the C–N bond formation using powerful tool in its armory, the "H-bonding". Reactions were conducted in the absence of an external catalyst or co-solvents and, hence, are a greener approach in organic synthesis. The reactions of 15 examples were conducted with a variety of substrates to afford the addition products in the range of 70–95% yield. Theoretical studies on the transition state analysis suggested that it was the assistance of water, through H-bonding, that facilitated the conjugate addition of amine and proton transfer from ammonium ion, which could happen through two equally possible pathways. Graphical abstract: Image 1 Highlights: The aza-Michael reactions were conducted in water without catalyst. The quantitative yields of products were obtained at room temperature. 15 examples were conducted with a variety of substrates to afford 70–95% yields. Density functional theory (DFT) calculations were done to probe the role of water. DFT suggested C–N bond formation was catalyzed by water via H-bonding.